Effect of typhoons on the abundance and composition of phytoplankton in coastal waters of San Pedro Bay from 2012 to 2015 - Peralta, Jean Grace T.; Yap-Dejeto, Leni G. (2016)
Marine phytoplankton, as primary producers, play a primary role in the ecology of the marine ecosystem and changes in their pattern of distribution and abundance can have significant impacts on the entire ecosystem. Environmental changes cause shifts in phytoplankton composition, their productivity and the status of their ecosystem. This study tracked the changes in phytoplankton cell densities and composition in San Pedro Bay from 2012-2015 taking note of the effect of typhoons. All water samples were taken one meter below the water surface from three stations. For cell density determination, three 1L water samples were collected with the use of WILDCO sampler. Afetr a typhoon occurrence, the general trend was manifested by an increase in phytoplankton cell density. For instance, on December 2014, 16 days after Typhoon Hagupit/Ruby struck the bay, phytoplankton cell density dominated by Skeletonema spp. (3.7 plus or minus 0.09 x 10 raised to the power of four cells/L), increased to 12 plus or minus 0.09 x 10 raised to the power of 4 cells/L. Physico-chemical parameters from samples taken weeks after a typhoon occurrence in San Pedro Bay were often an increase in dissolved oxygen, temperature, salinity, pH, nutrient and chlorophyll-a concentrations.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.
Keywords: Science and technology